Estimating the Surface Runoff Volume of the Wadi AL Washash Basin in Al-Alam District Using the (CN-SCS) Method - Mahidi, Emad Hameed; Hamid Al-Jubouri, Dili Khalaf (Journal of Tikrit University for Humanities, 2024)
The research is based on the (Cn-Scs) method, which is one of the important methods used to estimate water harvest and which was developed by the Department of Conservation of Agriculture in the United States of America (Runoff Curve Number), which is abbreviated into (RCN) in the year 1970 and its final formulation was developed. In 1986, one of the features of this system is its accurate and comprehensive coverage of all uses of the Earth’s surface in addition to give a clear and accurate picture of soil moisture in advance as well as the extent of the porosity and permeability of the soil. This is done by dividing the soil into four hydrological groups, as these categories show us the suitability of any of these four groups in the emergence of surface water flow, and that this model is distinguished by its high accuracy in this field. In order to obtain high accuracy and correct results, they were achieved through the model used. Remote sensing technology (REMOT SENSING) and geographical information systems were relied upon, as through these technologies it is possible to obtain the most accurate details of the surface runoff process. After completing these elements, the values ​​of (CN) were obtained which express the extent of soil permeability, the coefficient which expresses the maximum possibility of the soil retaining water, the coefficient ((LA) which expresses the amount of rainwater lost before the start of the surface runoff process, and the coefficients (2) and ((CV) which express the depth and volume of runoff.